Costs of non-metastatic prostate cancer treatment among privately insured men in the United States - Ashley J. Housten; Su-Hsin Chang; Hannah E. Rice; Allison J. L’Hotta; Eric H. Kim; Bettina F. Drake; Joanna L. Buss; Mary C. Politi (PLoS ONE, 2025)
Background Our objective was to quantify the cumulative total and out-of-pocket (OOP) costs for 3 non-metastatic prostate cancer treatment modalities: radiation, surgery, and conservative management at intervals of 1-, 3-, and 5-years post-diagnosis. We predicted these cumulative costs for a typical patient to improve cost transparency, facilitate conversations about potential costs, and to help advance non-metastatic prostate cancer cost evaluation. Methods We used Merative™ MarketScan® Commercial Database data from 2007–2020. The cumulative total costs evaluated from the healthcare sector perspective were patient, clinician, and system/facility costs. We used descriptive statistics to summarize the sociodemographic characteristics of the cohort and a multivariable regression model to estimate the association between each treatment option (radiation, surgery, conservative management) and costs with inverse probability of treatment weighting (IPTW) to account for potential selection bias. We then predicted total and OOP costs defined by sample mode characteristics. Results This cohort included 74,324 patients. Cumulative total and OOP costs were significantly higher for radiation (p < 0.0001) and for surgery (p < 0.0001) at Years 1, 3, and 5 compared to conservative management. For a typical patient, total cumulative cost estimates for conservative management at Years 1/3/5 were: $15,896/$33,436/$48,110 and the cumulative patient OOP costs were: $2,003/$4,540/$6,621. The cumulative total costs for surgery at Years 1/3/5 were: $38,348/$49,424/$60,885 and the cumulative OOP costs were: $2,980/$5,255/$7,221. The cumulative total costs for radiation at Years 1/3/5 were: $65,397/$77,859/$91,497 and the cumulative OOP costs were: $3,151/$5,481/$7,504. Conclusions For all years, the cumulative costs of radiation were highest, followed by surgery and conservative management, respectively. Radiation as the first treatment modality had higher costs compared to surgery and conservative management at the 3 time points. Impact These cost estimates support non-metastatic prostate cancer treatment related cost transparency. These estimates can help researchers evaluate costs and facilitate patient-clinician cost conversations.